Amulet Installation and Incense Burning Ritual in Sumenep Noble Society Residence - Asyim, Raden Bagus; Soedirham, Oedojo; Fatah, Mohammad Zainal (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Health is the very basic needs for every human being. Traditional health system is widely focused on treatment (curative), although there are other efforts, such as prevention (preventive), before treatment effort is done. Regarding the improvement of the public health status, this effort has a very strategic position, as it is cheaper in financing and easy in execution. This research was conducted to analyze the behavioral health concept of traditional cultures found in amulet installation and incense burning ritual in the residence. This research used qualitative method called phenomenology approach, whereas the research data were obtained using literature studeis and indepth interview. The result showed that amulet installation and incense burning ritual on the residence had the meaning to control lust for avoiding impulse behavior that was able to suffer the human life, regarding the fact that health was not only observed in physical aspects. However, if it was reviewed from the modern health science point of view, this behavior had to do with health and/or disease occurence. Factors that influenced health were from internal factor within the body, such as lust control and external factor, such as the environmental condition around the human being, whereas sickness was influenced by behavior, spells, environment, and destiny factors. The prevention efforts to stay healthy was with the natural human behavior and human capability in controlling lust.